Analysis of behavioral problems in children with sleep-disordered breathing and decreased REM sleep. (August 2021) - Yang, Liqiang; Zhou, Yilong; Zhong, Jianwen; Liu, Yuan; Qiu, Shuyao; Zeng, Jinhong; Liu, Dabo
Abstract: Objective: REM sleep is known to be closely associated with behavioral problems in children. Our previous study showed that children with decreased REM sleep (REM < 10%) suffered from severe sleep-disordered breathing (SDB). In this study we explored the characteristics of behavioral problems in children with SDB and decreased REM sleep. Methods: A total of 223 children were enrolled in the study. Sleep was evaluated by Polysomnography (PSG). Behavioral problems were assessed by a Chinese version of Child Behavior Checklist (parent-reported). Parameters of SDB and behavioral problem scores (internalizing, externalizing, and total scores) were compared between the children with decreased REM (REM < 10%) and those with REM ≥ 10% before and after controlling overweight/obesity and obstructive sleep apnea hypopnea syndrome (OSAHS). Parameters of SDB were also compared between the normal behavior group and the abnormal behavior group. The correlation between the behavioral problems and the sleep parameters was analyzed. Results: The children with decreased REM sleep (<10%) had more severe externalizing and total behavioral problems, even when controlled for overweight/obesity. The abnormal behavior group had significantly shorter total sleep time and REM sleep compared to the normal behavior group. Conclusion: Children with SDB and decreased REM sleep showed more severe behavioral problems, especially the externalizing behavioral problems. The behavioral problems can be aggravated by insufficient total sleep. Decreased REM sleep in children may be an independent parameter that is associated with the behavioral problems in children with SDB.